Physical activity, sleep, and C-reactive protein as markers of positive health in resilient older men. (September 2016) - Fields, Alison J; Hoyt, Robert E; Linnville, Steven E; Moore, Jeffery L
This study explored whether physical activity and sleep, combined with the biomarker C-reactive protein, indexed positive health in older men. Many were former prisoners of war, with most remaining psychologically resilient and free of any psychiatric diagnoses. Activity and sleep were recorded through actigraphy in 120 veterans (86 resilient and 34 nonresilient) for 7 days. Resilient men had higher physical activity, significantly lower C-reactive protein levels, and 53 percent had lower cardiac-disease risk compared to nonresilient men. Sleep was adequate and not associated with C-reactive protein. Results suggest continued study is needed in actigraphy and C-reactive protein as means to index positive health.